2017
DOI: 10.1016/j.cognition.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Auditory morphological processing: Evidence from phonological priming

Abstract: Using an auditory lexical decision task, we find evidence of a facilitatory priming effect for morphologically complex targets (e.g., snow-ed) preceded by primes which rhyme with the target's stem (e.g., dough). By using rhyme priming, we are able to probe for morphological processing in a way that avoids confounds arising from semantic relatedness that are inherent to morphological priming (snow/snow-ed). Phonological control conditions (e.g., targets code and grove for prime dough) are used to rule out alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This has also to be considered in the interpretation of the present findings. However, several studies presenting spoken prime words used comparable timing as in the present study and reported priming effects (Holcomb and Neville ( 1990 ) SOA = 1,420–1,850 ms, ISI = 1,150 ms; Voyer and Myles ( 2017 ) SOA = 800–1,000 ms, ISI = 50–250 ms; Kim and Sumner ( 2017 ) SOA = not indicated, ISI = 100 ms; Bacovcin et al ( 2017 ) SOA = not indicated, ISI = 400–600 ms). Holcomb and Neville ( 1990 ) even reported stronger priming effects for auditory (SOA 1,420–1,850 ms) than visual prime words (SOA 1,550 ms), which had even longer SOA.…”
Section: Discussionsupporting
confidence: 56%
“…This has also to be considered in the interpretation of the present findings. However, several studies presenting spoken prime words used comparable timing as in the present study and reported priming effects (Holcomb and Neville ( 1990 ) SOA = 1,420–1,850 ms, ISI = 1,150 ms; Voyer and Myles ( 2017 ) SOA = 800–1,000 ms, ISI = 50–250 ms; Kim and Sumner ( 2017 ) SOA = not indicated, ISI = 100 ms; Bacovcin et al ( 2017 ) SOA = not indicated, ISI = 400–600 ms). Holcomb and Neville ( 1990 ) even reported stronger priming effects for auditory (SOA 1,420–1,850 ms) than visual prime words (SOA 1,550 ms), which had even longer SOA.…”
Section: Discussionsupporting
confidence: 56%
“…Reaction time was our response variable. The fixed factors were condition (morphological, non-morphological and control), type (whether the elements in the pair were same or different), and duration (the duration, in milliseconds, of the second nonword in each pair, see Bacovcin et al 2017; Post et al 2008, for a similar procedure). We centered the continuous variable “duration” to minimize collinearity between predictors.…”
Section: Resultsmentioning
confidence: 99%
“…Though usually appearing in Austronesian, Austroasiatic and several Native American languages such as Tagalog, Khmer and Malay (Ultan, 1975;Moravcsik, 2000;Halle, 2001;Goudswaard, 2004;Wilson, 2014;Bacovcin & Freeman, 2016;Harizanov, 2017), infixation may also appear in languages such as English (7a-c) as a special and easily identifiable morphological process in that a morpheme is placed in the middle of a word (McCarthy, 1982;Yu, 2007Yu, , 2008Yu, , 2015. Regarding (7a-c), Yu (2007) claims that the expletives -bloody-, -fuckin-and -goddamninterrupt the bases, which turn into meaningless parts after infixation.…”
Section: True Vs False Infixationmentioning
confidence: 99%